THE EFFECT OF SALES PROMOTION ON BUYING INTEREST IN E-COMMERCE SHOPEE WITH TRUST AS INTERVENING VARIABLE - Eka Mayastika Sinaga (PT Inovasi Pratama Internasional, 2022)
This study aims to determine the effect of sales promotion on buying interest with trust as an intervening variable. Data was collected by giving questionnaires to 80 students as respondents. The data analysis technique used is multiple linear regression analysis and path analysis . Testing the first hypothesis, it can be seen that tcount (2.580) > ttable (1.994), as well as the significance value of 0.01 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the promotion variable (X) has a positive and significant effect on trust (Z). (2) Testing the second hypothesis, it can be seen that tcount (1.451) < ttable (1.994), and the significance value is 0.15 > 0.05, it can be concluded that the second hypothesis is rejected, meaning that promotion (X) has no positive and insignificant effect on buying interest (Y). (3) Testing the second hypothesis, it can be seen that tcount (3.575) > ttable (1.994), and the significance value is 0.00 <0.05, it can be concluded that the third hypothesis is accepted, meaning that trust (Z) has a positive and significant effect on buying interest. (Y). (4) Path analysis test shows the direct effect of variable X on variable Y of 0.163. Meanwhile, the indirect effect through the Z variable is 0.299 x 0.402 = 0.120. From the calculation results obtained, the indirect effect through the Z variable is smaller than the direct effect on the Y variable.